IN NORTH SUMATRA PROVINCE, AN ANALYSIS OF FARMER CHANGE RATES AND ECONOMIC GROWTH ON THE HUMAN GROWTH INDEX - Fithra Maharani; Lilis Saryani; Iswandi Idris (SEAN Institute, 2023)
Research urgency: North Sumatra's agricultural economic potential: North Sumatra is one of the provinces in Indonesia with quite large agricultural economic potential. Therefore, understanding how the farmer exchange rate and economic growth impact the human development index in this province is very important to know the extent to which the agricultural sector can influence economic growth and community welfare in the North Sumatra region. The important role of farmers in the economy: Farmers have a very important role in the Indonesian economy and are one of the main sectors that contribute to economic growth and poverty alleviation in rural areas. Therefore, increasing farmers' exchange rates and economic growth which has a positive impact on the human development index in North Sumatra Province can help improve the welfare of farmers and communities in the North Sumatra region. The importance of the human development index: The Human Development Index (HDI) is an indicator used to measure people's welfare, including health, education and income. Therefore, understanding the relationship between farmer exchange rates and economic growth with HDI in North Sumatra Province is very important to improve the welfare of the people in the North Sumatra region. The research objective of the analysis of farmer exchange rates and economic growth on the human development index in North Sumatra Province is to determine the relationship between farmer exchange rates and economic growth and the human development index in North Sumatra Province. To analyze the factors that influence farmer exchange rates and economic growth in North Sumatra Province. To analyze the factors that influence the human development index in North Sumatra Province. To provide policy recommendations that can increase farmers' exchange rates and economic growth as well as increase the human development index in North Sumatra Province. The results of the analysis show that there is a positive relationship between farmer exchange rates and economic growth in North Sumatra Province